Explaining Social Entrepreneurial Intentions among College Students in Zimbabwe - Rambe, Patient; Ndofirepi, Takawira Munyaradzi (Journal of Social Entrepreneurship, 2019)
While definitional clarity of social entrepreneurship as constituting a semblance of economic engagements that straddle entrepreneurial studies, social innovation and not for profit ventures had been established, the antecedents of such entrepreneurship are only beginning to emerge. This study tests moral obligation, empathy, self-efficacy and social support as main determinants of social entrepreneurial intentions in the depressed economy of Zimbabwe, where the pursuit of economic gains at a personal level is anticipated to thrive. The study employed the Mair and Naboa model, a quantitative approach, and survey design to explore the influence of the aforementioned antecedents on the social entrepreneurial intentions of a sample of 284 vocational training college students. Results suggest that only empathy, self-efficacy and social support had statistically significant relationships with social entrepreneurial intentions. Notably, social support had a negative predictive relationship with social entrepreneurial intentions. The outcome of the study partially validates the Mair and Naboa model.
Published Article
Keywords: Mair and Naboa; Social Entrepreneurial Intentions; Social Entrepreneurship; Students; Zimbabwe